Tell me who you are and I will give you my consent: A light-touch intervention on consent to data linkage - Joshua Fullard; Sonkurt Sen (University of Essex, Institute for Social and Economic Research (ISER), 2022)
Consent to data linkage (or the lack of it) has long been an important topic for researchers using survey data. In this paper, we use newly collected survey data to investigate the role that respondents' trust in the research team has on their propensity to consent to link their survey data to their educational, health and recreational administrative records. In addition, we investigate how participant consent rates di er by linkage topic and respondent characteristics. Finally, we experimentally vary the information respondents receive about the research team to investigate the role that information has on trust levels and consent rates. Our results show a strong positive relationship between respondents' trust in the research team and their propensity to consent to data linkage. Additionally, we nd that the provision of additional information about the research team has a positive e ect on respondents' trust, particularly those from an ethnic minority background. However, this increase in the respondents trust does not translate into higher consent rates.
Keywords: 330; Data Linkage; Consent; Light-touch Intervention